2006
DOI: 10.5194/acpd-6-9907-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air-sea fluxes of methanol, acetone, acetaldehyde, isoprene and DMS from a Norwegian fjord following a phytoplankton bloom in a mesocosm experiment

Abstract: Abstract. The ocean's influence on volatile organic compounds (VOCs) in the atmosphere is poorly understood. This work characterises the oceanic emission and / or uptake of methanol, acetone, acetaldehyde, isoprene and dimethyl sulphide (DMS) as a function of photosynthetically active radiation (PAR) and a suite of biological parameters. The measurements were taken following a phytoplankton bloom, in May/June 2005 with a proton transfer reaction mass spectrometer (PTR-MS), from mesocosm enclosures anchored in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 25 publications
(29 reference statements)
8
61
3
Order By: Relevance
“…This could be evidence of elevated DOM precursors or enhanced biologically mediated acetone production in this more productive region. Therefore, this could show agreement with the mesocosm experiments conducted by Sinha et al [2007], where a positive correlation was shown between acetone emissions to the atmosphere with photosynthetically active radiation (PAR) during a phytoplankton bloom.…”
Section: Photochemical Effectssupporting
confidence: 90%
“…This could be evidence of elevated DOM precursors or enhanced biologically mediated acetone production in this more productive region. Therefore, this could show agreement with the mesocosm experiments conducted by Sinha et al [2007], where a positive correlation was shown between acetone emissions to the atmosphere with photosynthetically active radiation (PAR) during a phytoplankton bloom.…”
Section: Photochemical Effectssupporting
confidence: 90%
“…Phytoplankton and atmospheric deposition are considered the primary sources of C1 compounds in surface seawater (Heikes et al, 2002;Sinha et al, 2007), but little information is available about their concentrations or seasonal trends that may lead to their availability as substrates for bacterioplankton. Methanol is the most abundant volatile organic compound in the lower atmosphere; however, processes influencing the atmospheric: marine flux are not well understood (Singh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, sources and sinks of methanol are not well defined for ocean surface waters (Heikes et al, 2002). Phytoplankton is postulated to be a source of methanol (Sinha et al, 2007), but measurements of productive phytoplankton communities in mesocosms suggest that even under these conditions seawater is a sink for atmospheric methanol (Sinha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%